Enterovirus 71 non-structural protein 3A hijacks vacuolar protein sorting 25 to boost exosome biogenesis to facilitate viral replication - Ruan, Zhihui; Liang, Yicong; Chen, Zicong; Yin, Jialing; Li, Chengcheng; Pan, Pan; Zhang, Qiwei; Wu, Jianguo; Luo, Zhen (Frontiers in Microbiology, 2022)
Human enterovirus 71 (EV71) is one of the major agents of the hand, foot, and mouth disease (HFMD), and occasionally causes severe neurological complications. There is clinical evidence that EV71 infection increases the exosomes in the serum of severe HFMD patients, suggesting a role of exosomes in EV71 pathogenesis. However, the relationship between exosomes and EV71 replication remains elusive. In this study, we initially found that EV71 infection elevated exosome biogenesis in the cultured cells. Among EV71 nonstructural proteins, we identified EV71 3A, but not 3B, constitutively promoted exosome secretion. In detail, EV71 3A protein interacted with VPS25 (vacuolar protein-sorting-associated protein 25), while knock-down of VPS25 reduced EV71 3A protein- and EV71- induced exosome production. Further studies revealed VSP25 located on exosomes and its expression correlated to the exosome production. During EV71 infection, knock-down of VPS25 decreased exosome biogenesis to attenuate viral replication. Consistently, GW4869, an exosome inhibitor, exerted an obviously antiviral activity against EV71 replication companied with the decrease of exosome secretion or formation. These findings suggest the binding of EV71 3A and VPS25 benefited exosome biogenesis, thereby boosting viral replication. This study uncovers a novel mechanism underlying EV71-mediated exosomes in the regulation of viral replication, which provides potential anti-viral strategies against the EV71 infection and transmission in HFMD.